Test-Retest Reliability of Discrete Choice Experiment for Valuations of QLU-C10D Health States - Gamper, E.; Holzner, B.; King, M.; Norman, Richard; Viney, R.; Nerich, V.; Kemmler, G. (Elsevier Inc., 2018)
© 2018 International Society for Pharmacoeconomics and Outcomes Research (ISPOR). Background: Recently, a newly developed cancer-specific multiattribute utility instrument based on the widely used health-related quality of life instrument, the European Organisation for Research and Treatment of Cancer QLQ-C30, was introduced: the QLU-C10D. For the elicitation of utility weights, a discrete choice experiment (DCE) was designed. Our aim was to investigate the DCE in terms of individual choice consistency and utility estimate consistency by applying a test-retest design. Methods: We conducted the study in general population samples in Germany and France. The DCE was administered via a web-based self-complete survey using online panels. Respondents were presented 16 choice sets comprising 11 attributes with 4 levels each. Retest was conducted 4 to 6 weeks after first assessment. We used kappa and percentage agreement as measures of choice consistency and both intraclass correlations and mean utility differences as measures of utility estimate consistency. Results: A total of 300 German respondents (31% female, mean age 48 years [SD 14]) and 305 French respondents (46% female, mean age 47 years [SD 16] ) completed test and retest assessments. Individual choice consistency was moderate to high (Germany: ? = 0.605, percentage agreement = 80.2%; France: ? = 0.411, percentage agreement = 70.6%). Utility estimate consistency was high when considering intraclass correlations (all > 0.79). Mean utility differences were 0.08 in the German sample and 0.05 in the French sample. Conclusions: Results indicate that the designed DCE elicits stable health state preferences rather than guesses or mood-specific or condition-specific judgments. Nevertheless, the identified mean utility differences between test and retest need to be taken into account when determining minimal important differences for the QLU-C10D in future research.